The Concept Of Informativity Between Syntax Of the Sentence And Syntax Of The Text/ مفهوم الإعلاميَّة بين نحو الجملة ونحو النص - Ali, Essam Tammam Abd El-Hamid; Al-Yatimi, Abdul Rahman Othman Mohammed (Ijaz Arabi Journal of Arabic Learning, 2025)
This study aims to establish the concept of informativity within Arabic syntax. It explores the definition of this term among textualists and highlights the differing opinions among Arab researchers regarding its translation despite a consensus on its meaning. The study also examines the levels of informativity recognized by the textualists. It elucidates the role of the audience in determining the informativity of a text based on their background knowledge, which enables them to anticipate the concepts and implications of the text. Furthermore, it identifies the sources of expectation that assist the audience in comprehending the text. The research then delves into the concept of informativity as understood by the Arabic grammarians, presenting the terms and expressions used to convey this idea. It reviews the criteria they established for achieving informativity within a sentence. The findings indicate that the grammarians understood informativity early, albeit with different terminology, such as benefit and reporting. They formulated criteria for assessing informativity in a text, which the study identifies as four key standards: novelty, the speaker's intention to inform, the completeness of the statement in terms of elements of prediction, and the appropriateness of silence. The research concluded that the concept of " informativity " differs between the textualists and the grammarians, with the former having a broader understanding. While grammarians limit informativity to achieving benefit, textualists consider it in terms of the recipient's expectations of the text's concepts versus the concepts the text conveys. Additionally, it was found that grammarians did not focus on establishing levels of informativity as the textualists did, who categorized it into three tiers. Furthermore, the grammarians addressed the boundaries of discourse about the concept of informativity, establishing the appropriateness of silence as a criterion for benefit or informativity.